Impact of COVID-19 pandemic on blood pressure management and antihypertensive medication use in hypertensive patients: Impact of COVID-19 on hypertension management - Beşişik Yilmaz, Zeynep Rumeysa; Beşişik Temel, Merve; Beşişik, Ayşe Gül; Yilmaz, Furkan; Mesçi̇ Banu (Journal of Surgery and Medicine, 2026)
Background/Aim: The interaction between angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and the angiotensin-converting enzyme 2 (ACE-2) system became a focal point during the COrona VIrus Disease-19 (COVID-19) pandemic, as SARS-CoV-2 utilizes ACE-2 for cellular entry. Concerns arose that renin-angiotensin-aldosterone sytem (RAAS) inhibitors, which modulate the ACE-2 system, might enhance viral entry by increasing ACE-2 expression. Despite some proposing alternative antihypertensives, other studies indicated potential protective effects of RAAS inhibition in lung injury models, underscoring the need for clarity on ACEI and ARB use during viral infections. Consequently, the European Society of Cardiology issued a statement in March 2020, asserting no clinical or scientific evidence justified halting ACEI or ARB therapy due to COVID-19. The recommendation was for physicians and patients to maintain their antihypertensive treatment regimens. This study aimed to evaluate the impact of the COVID-19 pandemic on the systolic and diastolic blood pressure levels of hypertensive patients, as well as to investigate any antihypertensive treatment modifications made due to the perceived risk associated with the use of ACIs and ARBs during the COVID-19 outbreak. Methods: A total of 500 hypertensive patients who had visited the Internal Medicine Clinic prior to March 2020 were surveyed by phone. The data collected from these patients included their age, the duration of their hypertension, the medications they were taking, their self-measured home blood pressure values both before and after the pandemic, their physician consultations, if any, and any changes that were made to their antihypertensive treatments during this time period. Results: Of the participants, 58.8% were women, with a mean age of 63.16 (10.87) years and hypertension (HT) duration of 7.87 (3.58) years. During the pandemic, 20% of the patients consulted a physician who opted not to alter the patients’ ACEI and ARB regimens. Prior to the pandemic, mean SBP and DBP were 131.38 (9.37) mmHg and 75.3 (6.07) mmHg, respectively. During the pandemic, mean SBP decreased significantly to 130.58 (9.04) mmHg (P=0.001), while DBP of 75.22 (6.05) mmHg remained statistically unchanged (P=0.853). Conclusion: The findings indicate that clinicians adhered to the European Society of Cardiology statements, retaining ACEI and ARBs. The significant decrease in SBP post-pandemic may be attributed to lifestyle changes.